Structure-Function Relationship of Inclusion Bodies of a Multimeric Protein - Singh, Anupam; Upadhyay, Vaibhav; Singh, Akansha; Panda, Amulya K. (Frontiers in Microbiology, 2020)
High level expression of recombinant proteins in bacteria often results in their aggregation into inclusion bodies. Formation of inclusion bodies poses a major bottleneck in high-throughput recovery of recombinant protein. These aggregates have amyloid-like nature and can retain biological activity. Here, effect of expression temperature on the quality of Escherichia coli Asparaginase II (a tetrameric protein) inclusion bodies was evaluated. Asparaginase was expressed as inclusion bodies at different temperatures. Purified inclusion bodies were checked for biological activities and analyzed for structural properties in order to establish a structure-activity relationship. Presence of activity in inclusion bodies showed the existence of properly folded asparaginase tetramers. Expression temperature affected the properties of asparaginase inclusion bodies. Inclusion bodies expressed at higher temperatures were characterized by higher biological activity and less amyloid content as evident by Thioflavin T binding and Fourier Transform Infrared (FTIR) spectroscopy. Complex kinetics of proteinase K digestion of asparaginase inclusion bodies expressed at higher temperatures indicated higher extent of conformational heterogeneity in these aggregates.